2014
DOI: 10.1097/qad.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Modified interferon-α subtypes production and chemokine networks in the thymus during acute simian immunodeficiency virus infection, impact on thymopoiesis

Abstract: Thymopoiesis is deeply impacted from the first days of SIV infection. Reduced thymocyte proliferation - a time-consuming process - together with modified chemokine networks is consistent with thymocyte differentiation speed-up. This may transiently enhance thymic output, thus increasing naive T-cell counts and diversity and the immune competence of the host. Nonetheless, long-lasting modification of thymic physiology may lead to thymic exhaustion, as observed in late primary HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…In keeping with recent observations in acutely HIV-infected humans (34, 47), absolute CD4 + T-cell counts remained stable in the gut mucosa during the first 2 weeks of SIV infection. By contrast, we showed that circulating CD4 + and CD8 + T-cell counts decreased rapidly in SIV-infected Chinese rhesus macaques, consistent with our previous observations (48). These results suggest that CD4 + and CD8 + T-cells homed into tissues.…”
Section: Discussionsupporting
confidence: 93%
“…In keeping with recent observations in acutely HIV-infected humans (34, 47), absolute CD4 + T-cell counts remained stable in the gut mucosa during the first 2 weeks of SIV infection. By contrast, we showed that circulating CD4 + and CD8 + T-cell counts decreased rapidly in SIV-infected Chinese rhesus macaques, consistent with our previous observations (48). These results suggest that CD4 + and CD8 + T-cells homed into tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, viral entry, viral replication kinetics, and the cytopathicity of HIV-1 in human thymocytes have been shown to be highly dependent on viral tropism, due to the predominance of CXCR4 (X4) versus CCR5 (R5) expression in the human thymus (9,12,13). Thymic disruption has also been described in nonhuman primate models of simian immunodeficiency virus infection (14).…”
mentioning
confidence: 99%
“…Thymus dysfunction is known to characterize HIV-1/SIV infections and contributes to their pathophysiology. In human thymus, thymocytes and medullary pDCs constitutively express IFNα and type I IFNs can suppress thymic output, further limiting CD4T cell recovery [82]. A strong alteration of both chemokines and IFNα subtype transcriptional patterns in SIV-infected thymuses was also recorded, and the IFNα subtypes produced in the infected thymuses inhibited thymocyte proliferation [82].…”
Section: Detrimental Effectsmentioning
confidence: 99%